Investigation of Seismicity Near Appin, NSW, and its Association With Mining, Geology, and Tectonics - Vasundhara (International Conference on Ground Control in Mining, 2001)
A chance detection of a seismic event of unexplained origin in the mining district of Appin in New South Wales. Australia, led to a detailed investigation of recording and analyzing seismic events occurring in the area. Multiple events were recorded each day on the seismometer stations. The larger events were strong enough to be recorded on a number of stations spread out in the district. Background investigation of seismicity stimulated due to engineering activities revealed that similar cases of mining triggered seismicity have been reported previously from many mining districts around the world. If the tectonic stresses are close to failure in a region then a small perturbation of the stress state may lead to instability in the region which may manifest itself as seismicity. The parameters that control the occurrence of such siesmicity include tectonic stress magnitudes and orientations. geological weaknesses or structural features and the amount of stress contribution due to mining. This paper reports on the seismic investigative study conducted in the Appin area and considers its association with the geological layout of the region and the mining activity.